Estudo dos efeitos da farinha de yacon e de Bifidobacterium lactis sobre as propriedades tecnológicas e funcionais do iogurte de leite de ovelha - Gusso, Ana Paula (2017)
Sheep milk has unrivaled characteristics for the elaboration of fine cheeses and yoghurts, since it is richer than the milk of the other species in almost all its components. Another food that stands out for its composition is the yacon root. Rich in fructan and phenolic acids this food has prebiotic and antioxidant effect, respectively. Sheep milk and yacon have characteristics in their composition that make them products of high nutritional and technological quality. In this context, the objective of the present work was the development and the evaluation of the technological and functional properties of a symbiotic yogurt of sheep's milk, using yacon flour (FY) as a prebiotic source and probiotic culture (Bifidobacterium lactis BLC 1). Initially the FY was produced, and its physical-chemical characterization was carried out to verify its prebiotic potential and its possible functional claims. The flour had significant contents of total dietary fiber and fructo-oligosaccharide (FOS), and it can be added in the manufacture of foods with potential of both fiber source and FOS. Therefore, the FY produced was used in the formulation of sheep milk yogurt, aiming at its symbiotic potential. The yogurts were characterized and the shelf life followed for 28 days. The results showed that it is possible to produce yogurts from symbiotic sheep milk, during the analyzed period. The sensorial analysis, combined with the physical-chemical and microbiological aspects allowed us to conclude that the best formulation for the next stage of this study would be yogurt with 5% FY and no sugar. This formulation was used as the basis for the preparation of control, prebiotic, probiotic and symbiotic ewes of sheep milk administered to four groups of Wistar male rats (n = 5). Ingestion via gavage was performed for 45 days, and after the experimental period the animals were euthanized and the serological, physical-chemical and microbiological and biomechanical analyzes were performed in the blood plasma, organs and femurs. The probiotic group presented a hypolipidemic effect in the animals according to the results obtained in the analysis of lipids excreted in feces, cholesterol content and serum triglycerides. Administration of Bifidobacterium lactis to the groups had no significant effect on bone mineral content. It is believed that the amount of FY supplemented to the yogurts was not enough to promote some expected benefits. However, FY administration promoted an improvement in the biomechanical properties of the femurs in relation to the probiotic and control groups. The development of food with functional claim are increasingly relevant in the context of disease prevention and quality of life improvement. The production of sheep milk derivatives has been growing in recent years, as have studies on the nutritional benefits of this raw material. The use of FY and sheep's milk has both technological and functional potential, and some studies are needed to better prove this claim.